Configurações para métodos de acesso por escaneamento - Mariano, Daniel Teodoro Gonçalves (2016)
The use of access technologies for communication, based on scanning methods, enables new communication opportunities for individuals with severe motor dysfunction. One of the most commom examples of this type of technology is the single switch scanning. Single switch scanning keyboards are often used as augmentative and alternative communication devices for inidividuals with severe mobility restrictions and with compromised speech and writing. They consist of a matrix of keys and simulate the operation of a physical keyboard to write messages. One of the limitations of these systems is their low performance. Low communication rates and considerable errors ocurrence are some of the few problems that users of these devices suffers during daily use. The development and evaluation of new strategies in augmentative and alternative communication are essential to improve the communication opportunities of user who make use of such technology. Thus, this work explores different strategies to increase communication rate and reduce user’s mistakes. Computational and practical analysis were performed for the evaluation of proposed strategies.